Point-of-care C-reactive protein and risk of early mortality among adults initiating antiretroviral therapy - CHAISSON, Lelia H. (AIDS, 2019)
OBJECTIVES: In resource-limited settings, mortality in the initial months following antiretroviral therapy (ART) initiation remains unacceptably high. Novel tools to identify patients at highest risk of poor outcomes are needed. We evaluated whether elevated C-reactive protein (CRP) concentrations predict poor outcomes among people living with HIV (PLWH) initiating ART. METHODS: We enrolled and followed for three-months consecutive PLWH with pre-ART CD4+ T-cell count ≤350 cells/uL initiating ART from two HIV clinics in Uganda. Pre-ART CRP concentrations were measured from capillary blood using a point-of-care (POC) assay. After excluding patients with prevalent TB—the leading cause of HIV death—we measured three-month mortality rates using Kaplan-Meier curves, used Cox regression to compare differences in survival, and used logistic regression to compare differences in the odds of opportunistic infections, between patients with and without elevated POC CRP (≥8 mg/L). RESULTS: Of 1,293 patients included (median CD4+ T-cell count 181 [IQR 82–278]), 23 (1.8%) died within three months, including 19/355 (5.4%) with elevated POC CRP and 4/938 (0.4%) with non-elevated POC CRP. Eighty-six (6.7%) patients were diagnosed with opportunistic infections, including 39/355 (11.0%) with elevated POC CRP and 47/938 (5.0%) with non-elevated POC CRP. Elevated POC CRP was associated with mortality (adjusted HR 10.87, 95% CI: 3.64–32.47) and opportunistic infection (adjusted OR 1.95, 95% CI: 1.23–3.07). CONCLUSIONS: Among PLWH with advanced HIV, elevated pre-ART POC CRP concentrations are associated with early mortality and opportunistic infections. Pre-ART POC CRP testing may reduce mortality by identifying patients at high risk for poor outcomes.